Formação inicial e trabalho docente em educação física: o que dizem os egressos sobre o mundo do trabalho no município de Belém-PA - LAUREIRO, Lauriany Oliveira (2022)
The present study deals with the Initial Formation and Teaching Work in Physical Education in the city of Belém-PA. The general objective was to analyze the relationship between the initial formation, the teaching work and their professional practice fields of graduates of the Physical Education undergraduate course of the Federal University of Pará, with specific objectives: To analyze the initial formation field in physical education in Brazil through the context of the productive restructuring and Analyze the initial formation and the configuration of the work in Physical Education through the Pedagogical Course Project and by the graduates. The problem question that guided the study was: What is the relationship between the initial formation and the teaching work of graduates of the Physical Education degree course at the Federal University of Pará? The methodology followed the criticaldialectical approach, according to Sanchez-Gamboa (2007), making use of field research with subjects participating in the Physical Education Degree course of the Federal University of Pará (UFPA), totaling 41 ( forty one) with the use of Google Formes online questionnaire tool. We did a bibliographic research about the debate of the initial formation in Physical Education and its reordering in the world of work, it was made a survey of the magazines Motrivivência, Think Practice, Movement and Brazilian Journal of Sport Sciences (RCBCE). The treatment of the data was made from the perspective of content analysis Franco (2011). The results revealed that there is a relationship between the initial formation in the course and their teaching work of the graduates, but with little compression analysis of the curriculum proposed by the institution, thus directing the formation to the fragmentation of knowledge focused on the demands of the world of education. job. We conclude that the study presents its relevance for the theme and for contributing to the Physical Education training project of the Federal University of Pará, as well as understanding how the graduates revealed their understandings about the initial education and the work they develop in their professional fields. in the municipality of Belém-PA.